Quality risk management during pharmaceutical 'good distribution practices' - A plausible solution - Nirmal Kumar; Ajeya Jha (Faculty of Pharmacy, Cairo University, 2018)
Quality of medicinal product is an important facet throughout lifecycle owing to its importance as acceptance criteria at customer's end. Drugs regulatory agencies have issued guidelines for quality risk evaluation, mitigation and review management. Quality risk management has become an integral part of quality management system at manufacturing plants. Procedures for deviation control, change control, investigations of market complaints and batch failures are dealt with the principle of quality risk management at the manufacturing facility. The exploratory study shows a dearth of research on quality risk management during supply chain operation, however, a few study has been carried out by keeping financial risk into account. This study addresses the gap in literature on quality risk management during supply chain operations. There are cases of unresolved customer complaints and batch failures originated due to inadequacies during distribution of pharmaceutical products. In absence of established quality risk management system during product shipment, there is no effective preventive plan related to risk factors. A corollary of manufacturing quality risk management has been drawn to the distribution of pharmaceutical products through this study. The quality risk management during pharmaceutical distribution may be useful to avoid market complaints, drug recalls, and regulatory actions. This study produces one unique model solution for industry professionals and policymakers opening a scope to reduce the product rejection thereby paving the way for substantial business growth.